Strategi Komunikasi Satuan Tugas Disabilitas Mental dalam Mengurangi Stigma Terhadap Caregiver ODGJ di Kecamatan Rubaru - Eka Nurjana Hartia Ningsih; Sri Wahyuningsih (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Stigma against people with mental disorders often extends to their families or caregivers (courtesy stigma). In Rubaru District, caregivers experience social pressure in the form of exclusion and ridicule, which hinders the patient's recovery process. The Mental Disability Task Force has developed a special communication strategy to address this phenomenon. Objective: to identify and analyze the communication strategies of the Mental Disability Task Force in reducing stigma against caregivers of people with mental disorders in Rubaru District. Methods: This article used a qualitative method with an instrumental case study approach. Data were collected through in-depth interviews, observations, and documentation. Informants were selected using purposive sampling techniques consisting of the Mental Disability Task Force, the Community Health Center Mental Health Officer (PJ Keswa), TKSK, and ODGJ caregivers. Data analysis was conducted using the Creswell model, which consists of six stages: collecting and organizing files for data, reading the entire text and forming initial codes, describing the case and its context, using categorical aggregation to form themes and patterns, interpreting the data, and presenting the data. Results: The Mental Disability Task Force implemented a communication strategy through the innovation of “Gersif Gasawa” (Family Mental Awareness Movement). This strategy includes stages of research, planning, implementation through door-to-door education and audio-visual media (NOBAR), to cross-sector reporting. The persuasive and interpersonal approach has proven effective in changing negative perceptions within the community into more supportive behaviors and acceptance of caregivers. The main obstacles encountered are resistance from some of the patients' families and limited understanding of mental health within the community. Conclusion: Integrated communication strategies based on local wisdom can reduce the level of social stigma against caregivers. Cross-sector collaboration is key to success in creating an inclusive environment for the recovery of people with mental disorders and the welfare of caregivers.